2013
DOI: 10.5489/cuaj.326
|View full text |Cite
|
Sign up to set email alerts
|

Variations between two 24-hour urine collections in patients

Abstract: Introduction: The current Canadian Urological Association (CUA) guideline recommends two 24-hour urine collections in the metabolic evaluation for patients with urolithiasis. The aim of the present study was to compare two consecutive 24-hour urine collections in patients with a history of urolithiasis presenting to a tertiary stone clinic. Methods: We retrospectively reviewed 188 patients who had two 24-hour collections upon presentation between January 2010 and December 2010. Samples were collected on consec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 7 publications
0
17
0
Order By: Relevance
“…7 Whereas the latter study used a single 24-hour urine collection, in the present study two 24-hour urine collections were used to get a better representative sampling of the urinary parameters as recommended by the Canadian Urology Association guidelines. 13,14 On the other hand, the study by Berlin and colleagues found that patients with high urinary calcium excretion (>6.0 mmol/L) had significantly higher levels of serum 25(OH)VD than those with a lower urinary calcium. 15 However, patients were prescribed neither VD nor calcium supplements.…”
Section: Discussionmentioning
confidence: 99%
“…7 Whereas the latter study used a single 24-hour urine collection, in the present study two 24-hour urine collections were used to get a better representative sampling of the urinary parameters as recommended by the Canadian Urology Association guidelines. 13,14 On the other hand, the study by Berlin and colleagues found that patients with high urinary calcium excretion (>6.0 mmol/L) had significantly higher levels of serum 25(OH)VD than those with a lower urinary calcium. 15 However, patients were prescribed neither VD nor calcium supplements.…”
Section: Discussionmentioning
confidence: 99%
“…Specific metabolic evaluation requires collection of two consecutive 24-h urine samples [13,14]. Patients should remain on a self-selected diet [15].…”
Section: Evaluation Of Patient Riskmentioning
confidence: 99%
“…21,22 Recent data suggests that up to 47.6% of patients had their clinical management changed by an abnormality that was identified only when two samples were collected. 23,24 It is currently recommended that two 24-hour urine collections be obtained in order to correctly identify metabolic abnormalities. The benefit of two collections should be balanced, however, by the practicality and importance of obtaining at least one collection (Level of Evidence 3, Grade C Recommendation).…”
Section: Number Of 24-hour Urine Collectionsmentioning
confidence: 99%